Analisis Efisiensi Teknis Produksi Ikan Pari Asap Pada Sentra Ikan Asap Kenjeran Kota Surabaya - Putra, Angga Pratama; Wijayanti, Regita Faridtunisa; Hayati, Nurul; Sulistiawati, Ani; Sutrisno, Sutrisno; Winiastri, Dinda (Lembaga Dongan Dosen, 2024)
The aim of this research is to analyze the achievement of the level of technical efficiency and the factors that influence the stingray smoking business at the Kenjeran Smoked Fish Center, Surabaya City. The research method used is the survey method. The data analysis method uses descriptive analysis and frontier production functions. Production inputs are stingrays, ice, water, wrapping leaves, fuel, food coloring, bamboo clamps and labor. The sampling technique used a census technique of 23 people. The average age of smoked stingray producers in Kenjeran is 42 years. In terms of education, the average education level of producers reaches 8 years. Meanwhile, the average experience of producers in the smoked stingray business is 8 years. The gamma value obtained was 0.131 and was not significant. This shows that 13.1 percent of the variation in smoked stingray production in Kenjeran is caused by differences in technical efficiency, while the remaining 86.9 percent is influenced by significant external factors and is outside the producer's control. The results of the partial test (t test) on the production function indicated that the number of fish, clean water, bamboo clamps, wrapping leaves, and labor significantly influenced the production of smoked stingrays in Kenjeran. However, the estimation results show that the age variable does not have a significant influence on the level of business inefficiency. Apart from that, education and experience variables also do not statistically influence the level of inefficiency of smoked stingray producers. Analysis of technical efficiency levels shows that the technical efficiency values ​​achieved by producers range from 0.953 (minimum value) to 0.998 (maximum value), with an average of 0.984. Of the 23 smoked stingray producers analyzed, 13 producers (56.52 percent) had an efficiency level above the average, while 10 other producers (43.48 percent) were below the average level of technical efficiency.